Assessment of Left Atrial Mechanics in Patients with Preexcitation Syndrome Scheduled for Catheter Ablation. Issue 2 (24th August 2015) - Karakoyun, Süleyman; Tanboğa, Ibrahim Halil; Gökdeniz, Tayyar; Lazoğlu, Zakir; Topçu, Selim; Karal, Hüseyin; Aksakal, Enbiya; Sevimli, Serdar
Abstract : Objectives: We aimed to test the left atrial (LA) mechanics and contraction synchrony by 2D strain imaging, in patients with Wolff–Parkinson–White (WPW) syndrome, before and after radiofrequency catheter ablation (RFCA). Methods: Study population consisted of 25 patients with WPW scheduled for RFCA and 30 healthy controls. The peak LA strain at the end of the ventricular systole (LAs strain) and the LA strain with LA contraction (LAa Strain) were obtained. To assess LA dyssynchrony, septal versus lateral wall time‐to‐peak strain measurements were measured. Results: There was no difference between the patients with WPW and control subjects with regard to peak LAs and LAa strain. Patients with WPW demonstrated higher global time‐to‐peak LAs and LAa strain values compared with the control group. Peak LAs strain and LAa strain values, measured before and after the RF ablation of the accessory pathway, were comparable (34.3 ± 3.92 vs. 34.6 ± 3.2, P = 0.816, 14.7 ± 2.8 vs. 15.3 ± 2.3, P = 0.052, respectively). Global time‐to‐peak LAs and LAa strain measurements were significantly shorter after the RFCA compared with the values obtained before the RFCA. However, septo‐lateral times to peak LA strain differences were found to be comparable in both WPW versus control and pre‐ versus postablation groups. Conclusion: LA mechanical function assessed by 2D strain imaging was comparable between patients with WPW and control subjects. Patients with WPW had more prominent LA dyssynchrony during atrial pump phase as compared with the controls, a condition which could not improve after successful elimination of the accessory pathway by RFCA.